PROMOTING REGIONAL INTEGRATION THROUGH HIGHER EDUCATION: LEGAL ANALYSIS ON THE EMPOWERMENT OF FOUNDATION IN PRIVATE UNIVERSITIES - Gunadi, Ariawan (UI Scholars Hub, 2016)
Higher education holds an important role in developing nation to build the manpower capacity of young generation and generate intellectual property. The same case applies in Indonesia as the most populous country in South East Asia with unmanaged higher education. Originally set out as a social entity which is engaged in nonprofit activities, some foundations have engaged in higher education. However conflict arises when the purpose of foundation is skewed for personal use that ended up disparaging other good foundations and the society in general. These issues prompted the government to promulgate Law No. 16 of 2001 regarding the Foundation and Law No. 28 of 2004 regarding the Amendment of Law No. 16 of 2001 regarding the Foundation. With this legislation, the foundation is expected to carry out specific standard and policies in managing their activities especially in order to prevent internal and external interference This article discusses on four parts: i) thetheoretical legal background of foundation in Indonesia compared to other legal entities; ii) the exposition of organs on the foundation in such as the Board of Trustees, Board of Executive and Board of Supervisory; iii) The analysis of role between foundation and universities, including examples of internal and external conflict as study case; and iv) the role of foundation to enhance Indonesia’s regional position in the international community.